From rhetoric of quality to criteria of legitimacy: The case of the Geneva primary school, 2005-2015 - Maulini, Olivier; Capitanescu Benetti, Andreea; Clénin, Julien; Périsset, Danièle; Perrenoud, Olivier; Progin, Laetitia; Marques, Roberta Smania; Veuthey, Carole (Swiss Journal of Educational Research, 2018)
Between 2005 and 2015, the Geneva primary school system was involved in a period of structural innovation. This was presented as a ‘reorganization’ intended ‘to improve the quality of teaching’. The reorganisation included placing principals in school to manage the establishments, school projects, boards of education and a network of priority education. Through analysis of the official texts and their impact within the evolution of these changes four criteria were brought to the foreground. This led to legitimization of public action regarding education: the fact to assure social stability, to satisfy teachers, to convince politically and to transcend the discussions. These results show that the symbolic virtues of every measure are tested by a political rationality which seems to owe, not only give satisfaction to sectorial interests, but also compose between their contradictory expectations.